13th InterSociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems 2012
DOI: 10.1109/itherm.2012.6231543
|View full text |Cite
|
Sign up to set email alerts
|

Crust removal and effective modulus of aligned multi-walled carbon nanotube films

Abstract: Carbon nanotubes (CNTs) have been attractive materials because of the unique combination of their small size and physical properties, such as high thermal conductivity and mechanical compliance. This paper extracts in-plane modulus of 100-220 µm-thick vertically aligned multi-walled carbon nanotube (VA-MWCNT) films. The films have low modulus in the range of 0.5-2 MPa, consistent with expectations due to the direction of CNT alignment. We study the effect of a top crust of entangled CNTs on the modulus by etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Past work shows a clear trend of decreasing in-plane modulus with increases in film thickness ranging from 0.5-200 µm [12,13]. This is attributed to the presence of a thin and entangled crust layer as described above.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Past work shows a clear trend of decreasing in-plane modulus with increases in film thickness ranging from 0.5-200 µm [12,13]. This is attributed to the presence of a thin and entangled crust layer as described above.…”
Section: Resultsmentioning
confidence: 65%
“…These results suggest that the overall density, roughness, array height, and other physical characteristics may strongly influence the mechanical properties of VACNT films. Previous measurements of the inplane modulus of VACNT films also suggested that the wide distribution of modulus values stem from the variation of nanostructural features [12,13]. The nonhomogeneous characteristics of VACNT films have been confirmed by several studies using various types of measurements, such as scanning electron microscopy (SEM), resonant Raman spectroscopy, and angle-resolved x-ray absorption [14][15][16][17][18].…”
Section: Nonhomogeneous Morphology and The Elastic Modulus Of Aligned...mentioning
confidence: 78%
See 1 more Smart Citation
“…VACNT growth is initially randomly oriented, until the growth forces a self-oriented vertical alignment. 11,17 Crust layers of tangled CNTs 17 and of amorphous carbon 18,19 can be formed on top of the VACNTs during growth. When the crust layer is removed so that incident radiation impinges directly on the VACNT surface, the reflectance of the VACNTs decreases.…”
Section: Discussionmentioning
confidence: 99%